MEMAHAMI KEDALAMAN KRISIS DAN DINAMIKA BUNUH DIRI MELALUI NOVEL THIRTEEN REASON WHY BY JAY ASHER DAN IMPLIKASINYA PADA LAYANAN KONSELING - Djohar, Tsamara Ramadhan Maulidah Hadhna; Salsabila, Ulyah; Nisa, Putri Zakiatun; Rahayu, Yasmin Fathia; Prameswari, Paramitha; Oktasari, Maria (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
This research explores the representation of suicide in the novel Thirteen Reason Why by Jay Asher and its implications for adolescent mental health. Using a social psychology theoretical framework, this study examines the impact of book narratives on understanding and behavior of suicide. This analysis identified factors such as bullying, harassment, and social isolation as contributors to suicidal behavior. The results of this study reveal that the factors causing suicide may be related to a lack of attention to the mental health of teenagers in the surrounding environment. Additionally, it was found that problems that may seem trivial, if not treated well, become potentially fatal if not treated well. In the novel Thirteen Reason Why, it is found that defamation, bullying, sexual harassment, depression and social problems need to receive more serious attention at all levels of society, especially in the school environment. This research applies a qualitative approach method using content analysis, opening up opportunities for in-depth understanding of the issues underlying teenage suicide. Through this approach, it is hoped that more effective solutions can be found in overcoming the mental and social problems faced by teenagers in the school environment.